Environmental Governance, Social Participation, and Sustainable Coastal Tourism in Eastern Indonesia - Wahab Tuanaya (Baileo: Jurnal Sosial Humaniora, 2026)
Coastal areas in Eastern Indonesia possess significant ecological and economic potential through mangrove-based ecotourism development. Nevertheless, sustainable coastal tourism remains challenged by environmental degradation, limited community participation, weak institutional collaboration, and the persistent tension between environmental conservation and local livelihood needs. This study examines environmental governance practices and social participation in the development of sustainable coastal tourism in Waiheru Village, Ambon City. Employing a qualitative case study approach, data were collected through observation, in-depth interviews with village authorities, youth organizations, community leaders, coastal residents, visitors, and relevant stakeholders, as well as documentation of environmental policies and tourism initiatives. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing, supported by triangulation and member checking to ensure validity. The findings reveal that collaborative environmental governance enhances mangrove conservation and promotes sustainable coastal tourism through active community engagement. Youth organizations play a strategic role in mobilizing participation, strengthening environmental awareness, and reinforcing local social capital. In addition, village regulations and collective monitoring mechanisms contribute to ecosystem protection and local economic empowerment. This study offers a novel contribution by integrating environmental governance, social participation, and sustainable tourism into a community-based governance framework within the socio-cultural context of Eastern Indonesia.